EFFECT OF LEVERAGE, PROFITABILITY, INTENSITY OF FIXED ASSETS, INVENTORY INTENSITY AND INDEPENDENT COMMISSIONER ON TAX AGGRESSIVENESS (Empirical Study on Manufacturing Companies Listed on the Indonesia Stock Exchange for the Period 2015 – 2019) - Erlina Erlina; Indah Umiyati; Sri Mulyati (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2022)
This study aims to examine whether there is a relationship between Leverage, Provitability, Fixed Asset Intensity, Inventory Intensity and Independent Commissioner on Tax Aggressiveness. This research was conducted by examining the annual reports of manufacturing companies listed on the Indonesian stock exchange for the period 2015 – 2019. The research method used in this study is a causal associative quantitative study. Hypothesis testing using the Econometric Views (E-Views) application The results show that leverage, fixed asset intensity, inventory intensity and independent commissioners have a positive effect on tax aggressiveness, while profitability has a negative effect on tax aggressiveness.